(untitled) (Eduscotech, 2023)
This research investigates the application of the Cooperative Learning model, specifically the Student Teams-Achievement Divisions (STAD) model, to improve mathematics learning outcomes for third-grade students at SDN Sukowinangun 1. The study adopts a quantitative approach with a correlational design, involving 120 fifth-grade students from SDN Munjung as the sample. Data collection was carried out using questionnaires, observations, and documentation of students’ mathematics scores, followed by analysis using multiple linear regression to assess the impact of independent variables on mathematics learning outcomes. The results indicate that: (1) parental involvement has a significant positive effect on students’ mathematics learning outcomes; (2) learning motivation acts as a mediator that strengthens the influence of parental involvement on academic performance; and (3) the combination of parental attention and learning motivation significantly contributes to improving students’ mathematics achievements. This study emphasizes the importance of holistic parental involvement and the implementation of learning strategies that support students’ intrinsic motivation.